POLITIK IDENTITAS ETNIS DAN AGAMA PARTAI ACEH DALAM QANUN BENDERA DAN LAMBANG ACEH - Amalia Sari, Ovi; Maryanah, Tabah; Cahyadi, Robi (Sekolah Tinggi Ilmu Syrari’ah Daru ‘Ulum (STSDU) Lampung Timur., 2022)
This study aims to (1) find out that the Aceh Party identifies the identity of Acehnese ethnically and religiously (2) analyze the identity of Acehnese citizens that needs to be manifested in the symbols of the Aceh Flag and Coat of Arms (3) determine the Aceh Party’s (PA) response to the rejection of the draft Qanum Flag and Coat of arms of Aceh by the Central Government and Acehnese ethnic minorities.The research method uses qualitative methods with descriptive research types. The informant determination technique used is the purposive sampling technique. Data collection tools used in the form of in-depth interviews and documentation studies. The data analysis technique used is data reduction, data display, verification. The results showed that (1) PA identifiet the Acehnesethnically and religiously besed on language indicator; customary institutions, customs and art; social control and, (2) The identity of the Acehnese people contains meaning and values that can be applied both as a unifying symbol and as a symbol of peace (3) There is a difference of opinion beween the Aceh Party in the DPRA and the Central Government regarding the Qanun on the Aceh Flag and Coat of Arms (4) The action of etnic minorities against the Qanun on the Aceh flag and symbol divided into two parts, namely some support and some oppose.Based on this explanation, it is known that the draft qanun on the Aceh flag and symbol is strongly influenced bay the PA’s identity politics and the are differences in understanding between the Aceh Government and the Central Government, the Aceh Governmen and some etnic minorities, so that it is not yet effective for application.